Elevated Preattentive Affective Processing in Individuals with Borderline Personality Disorder: A Preliminary fMRI Study - Baskin-Sommers, Arielle R.; Hooley, Jill M.; Dahlgren, Mary K.; Gönenc, Atilla; Yurgelun-Todd, Deborah A.; Gruber, Staci A. (Frontiers in Psychology, 2015)
Background: Emotion dysregulation is central to the clinical conceptualization of Borderline Personality Disorder (BPD), with individuals often displaying instability in mood and intense feelings of negative affect. Although existing data suggest important neural and behavioral differences in the emotion processing of individuals with BPD, studies thus far have only explored reactions to overt emotional information. Therefore, it is unclear if BPD-related emotional hypersensitivity extends to stimuli presented below the level of conscious awareness (preattentively). Methods: Functional magnetic resonance imaging (fMRI) was used to measure neural responses to happy, angry, fearful, and neutral faces presented preattentively, using a backward masked affect paradigm. Given their tendency toward emotional hyperreactivity and altered amygdala and frontal activation, we hypothesized that individuals with BPD would demonstrate a distinct pattern of fMRI responses relative to those without BPD during the viewing of masked affective versus neutral faces in specific regions of interest (ROIs). Results: Results indicated that individuals with BPD demonstrated increases in frontal, cingulate and amygdalar activation represented by number of voxels activated and demonstrated a different pattern of activity within the ROIs relative to those without BPD while viewing masked affective versus neutral faces. Conclusions: These findings suggest that in addition to the previously documented heightened responses to overt displays of emotion, individuals with BPD also demonstrate differential responses to positive and negative emotions, early in the processing stream, even before conscious awareness.